Disputable texts: pedagogies - Demo, Pedro (Revista Hipótese, 2015)
In tribute to the pedagogues, I here a defense of pedagogy. It is one of the most decadent courses today, but it is the most important. Just as it makes sense to ensure that education is fundamental to the economy and wage improvement, and maintain teacher earning very badly, it does not make sense proclaim the challenges of intensive knowledge society and maintain its greatest protagonist - the teacher - marginalized.
Keywords: Pedagogy; Education; Knowledge